Convergence of mammalian RQC and C-end rule proteolytic pathways via alanine tailing - Thrun, Anna; Garzia, Aitor; Kigoshi-Tansho, Yu; Patil, Pratik Rajendra; Umbaugh, Charles Samuel; Dallinger, Teresa; Liu, Jia; Kreger, Sylvia; Patrizi, Annarita; Cox, Gregory A.; Tuschl, Thomas; Joazeiro, Claudio A. P. (Molecular cell, 2021)
Incompletely synthesized nascent chains obstructing large ribosomal subunits are targeted for degradation by ribosome-associated quality control (RQC). In bacterial RQC, RqcH marks the nascent chains with C-terminal alanine (Ala) tails that are directly recognized by proteasome-like proteases, whereas in eukaryotes, RqcH orthologs (Rqc2/NEMF [nuclear export mediator factor]) assist the Ltn1/Listerin E3 ligase in nascent chain ubiquitylation. Here, we study RQC-mediated proteolytic targeting of ribosome stalling products in mammalian cells. We show that mammalian NEMF has an additional, Listerin-independent proteolytic role, which, as in bacteria, is mediated by tRNA-Ala binding and Ala tailing. However, in mammalian cells Ala tails signal proteolysis indirectly, through a pathway that recognizes C-terminal degrons; we identify the CRL2KLHDC10 E3 ligase complex and the novel C-end rule E3, Pirh2/Rchy1, as bona fide RQC pathway components that directly bind to Ala-tailed ribosome stalling products and target them for degradation. As Listerin mutation causes neurodegeneration in mice, functionally redundant E3s may likewise be implicated in molecular mechanisms of neurodegeneration.
Gesehen am 14.09.2022